Exploring the anti-diabetic potential of stevia-derived compounds through PPAR-γ targeted molecular docking - Putri, Amalia Sonita; Prawicha, Ertika Agtha; Putri, Esterike Alfatien; Wulandari, Indah; Saputri, Mutiara Anggun; Syakilla, Nadia Nur; Hidayati, Putri Aulia Nurul; Auli, Winni Nur; Saputro, Anjar Hermadi (Pharmacy Reports, 2023)
This study explores the potential of Stevia rebaudiana Bertoni-derived compounds as anti-diabetic agents by targeting the peroxisome proliferator-activated receptor gamma (PPAR-γ), a key regulator of glucose metabolism. Utilizing in silico molecular docking, we evaluated the binding affinities of four stevia-derived compounds (dulcoside A, steviol, isosteviol, steviolmonoside) and compared them to the native ligand (J35) and the well-known PPAR-γ agonist, rosiglitazone. Isosteviol exhibited the strongest binding affinity to PPAR-γ, with a binding energy of -8.89 kcal/mol, surpassing that of rosiglitazone (-8.26 kcal/mol) and closely following the native ligand (-9.01 kcal/mol). The interactions between isosteviol and PPAR-γ included multiple hydrogen bonds and hydrophobic interactions. These findings indicate that isosteviol, along with other stevia-derived compounds, has a potential as a natural anti-diabetic agent.